تأثير علاج القلس المعدي المريئي عند مرضى الربو - ديب, غزل; الحكيم, أمل; ديب, آلاء (Latakia University Journal -Medical Sciences Series, 2019)
شملت الدراسة 45 مريضاً ربوياً قبلوا في قسم الأطفال في مشفى الأسد الجامعي (اللاذقية) خلال عام واحد (2007-2008). تم تقييم الربو على مدى 3أشهر قبل وبعد علاج القلس, بلغ عدد المرضى الذين لديهم دليل للإصابة بالقلس مثبت بالتنظير الهضمي العلوي25 مريضاً ( 56%) وخضع جميعهم لعلاج القلس. بينما كان التنظير طبيعياً عند 20 مريضاً خضع 10 منهم لعلاج تجريبي للقلس بينما بقي الـ 10 الآخرون كعينة شاهد. جميع المرضى المصابين بالقلس أبدوا نقصاً واضحاً في استخدام الأدوية الربوية بعد علاج القلس وأوقفواالعلاج بمضاد اللوكوترين بنسبة 100%(P<0,05). أظهر3 مرضى 30)%) غير مصابين بالقلس وخضعوا لعلاج القلس هذا النقص وأوقف5 مرضى(50%) مضاد اللوكوترين. ولكن لم يبد أي مريض غير مصاب بالقلس ولم يخضع لعلاج تجريبي للقلس أي نقص هام في أدوية الربو وأوقف مريض واحد (10%) مضاد اللوكوترين(P=0,05). أي أن علاج القلس المعدي المريئي عند مرضى الربو المصابين بالقلس فعال في إنقاص الأدوية الربوية. The aim of this study was to evaluate the effect of anti GER treatment in asthmatic patients with GER. Asthma outcome was evaluated in 45 asthmatic patients 3 months before and after anti-GER treatment; they were hospitalized for one year (2007-2008) in the Pediatrics Department at AL-ASSAD University Hospital in Latakia. 25 patients (56%) with endoscopic evidence of GER underwent anti GER treatment. 20 patients had normal endoscopy; 10 of them underwent empirical anti-GER treatment, and the others were a control group. The results showed that all patients with GER had a significant reduction in asthmatic medication after anti-GER treatment and stopped antileukotrien100% (P < 0.05). 3 patients (30%) without GER but treated with anti GER treatment showed reduction, and 5 patients (50%) stopped antileukotrien; none of the control group showed any significant reduction in asthma medications, but one patient (10%) stopped anti leukotrien (P=0.05). To conclude, anti GER treatment in asthmatic patients with GER was effective in reducing asthma medication.